Nanoporous CoO Nanowire Clusters Grown on Three‐Dimensional Porous Graphene Cloth as Free‐Standing Anode for Lithium‐Ion Batteries. Issue 7 (26th February 2020) - Zhou, Chencheng; Liu, Jinzhe; Guo, Shouzhi; Zhang, Peilin; Li, Shuo; Yang, Yun; Wu, Jing; Chen, Luyang; Wang, Mingyi
Abstract: To further improve the capacity, charge rate and cycling stability has become urgent issues to be solved for lithium‐ion batteries (LIBs). In our study, we have synthesized nanoporous CoO nanowire clusters on three‐dimensional (3D) porous graphene cloth (denoted as CoO‐NW@GC) via a facile hydrothermal reaction and subsequent annealing process. The self‐supported graphene cloth is provided with large surface area, high porosity and superior electric conductivity, which can greatly contribute to the fast electron and ion transport. Due to the nanoporous CoO nanowire clusters uniformly in situ depositing on the robust 3D skeleton of GC substrate, the CoO‐NW@GC hybrid as anode for LIBs achieves 1190 mAh/g and 429 mAh/g under the current densities of 0.2 A/g and 3.2 A/g, respectively. After more than 200 cycles at a current density of 0.5 A/g, the capacity still maintains 1100 mAh/g. The CoO‐NW@GC illustrates high specific capacity, good stability as well as excellent rate performance. Abstract : Stand free : Nanowire clusters like CoO disposition uniformly on three‐dimensional graphene cloth (CoO‐NW@GC) with a solvothermal method and as an integrated electrode for LIBs. The nanowire clusters structure and a large number of nanopores expose countless active sites and result in a large specific surface. The composite material exhibits a high specific capacitance of over 1300 mAh/g at a current density of 0.2 A/g and durable cycle performance that even no capacity decreasing after 200 cycles.